PENGARUH KUALITAS KOMUNIKASI TELEMARKETING PT. ASURANSI XYZ TERHADAP KEPUASAN PELANGGAN DALAM MENDAPATKAN INFORMASI NASABAH ASURANSI KESEHATAN X DI JAKARTA - Mariani Mariani (Universitas Mercu Buana, 2019)
The development of information technology is expected that companies can create a variety of innovations so as not to decline. The research objective is to find out how much influence the quality of telemarketing communication on customer satisfaction X health insurance PT XYZ Insurance. The independent variable in this study is the quality of communication (X) with the concept of Joseph de Vito's theory (1997), and the dependent variable is customer satisfaction (Y) with the theory of Kotler, Keller (2008). This research uses a quantitative approach with a comparative causal type. The method used was a survey by distributing questionnaires. Sampling technique from a total population of 138 inpatients. The technique used in this study is total sampling where sampling is the same as the existing population. The results showed that the influence of communication quality on customer satisfaction health insurance X amounted to 0.27%, and the remaining 99.73% was influenced by other factors.